TATA LAKSANA âBEHAVIORAL ACTIVATIONâ PADA PASIEN JANTUNG KORONER - , RUKIANA HUTAGALUNG ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Heart disease is one of chronic diseases prevalent in the community. The data from Riset Kesehatan Dasar 2007 released by Ministry of Health indicate that the national prevalence of heart disease by 7.2 % and can occur at any age. In patients with coronary heart disease (CHD), depression may be a risk factor as well as factor that increase morbidity and mortality. Until now, there is no tritmen guideline for psychologist to deal with depression in patients with CHD. Behavioral Activation (BA) may be an appropriate alternative therapeutic therapy to decrease depression level in patients with CHD. BA is a technique that consists of various series of activities that can make someone feel happy, productive, and adjust to patient's value of life. This study aim is constructing Behavioral Activation guideline for decreasing depression level in patients with CHD validated by panelists. This research uses the Delphi method for data processing. Keywords: treatment guidelines, chronic illness, coronary heart disease, behavioral activation